The Use of Introspection in the Study of Problems Relating to Interpretation from Japanese to English - Chin, Ng Bee; Obana, Yasuko (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractIntrospection has been used widely to study translation processes in Indo-Europeon languages. In this study, the method of introspection was adapted to study interpretation processes in Japanese-English interpretation. Seven native speakers of English with varying levels of competence in Japanese-English interpretation skills took part in this study. The results indicate that rather than vocabulary, a better knowledge of argument and structure of the target language is essential for proficient interpreting. This is especially crucial when the topic of interpretation calls for the use of formal Japanese, as in the case of this study. As Japanese is a language which is characterized by the use of different registers and styles for different occasions, the findings of this study suggest that in the context of conference interpreting, student interpreters could benefit from increased exposure to the use of formal Japanese.